1997
DOI: 10.1111/j.1365-2672.1997.tb03593.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody detection of Clostridium microcolonies directly on membrane used for milk filtration

Abstract: 1997. The normal procedure for bacterial colony detection requires a nitrocellulose transfer step after membrane filtration and culture to prevent the development of a high background during the immunodetection. In this paper, we describe a modification of the basic protocol that omits the transfer step and reduces the risk of background. Previous observations indicated that interactions between milk components (principally cream) and membrane are responsible for the high non-specific staining observed. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The monoclonal antibody 21E7-B12 was used in an immunoenzymatic assay for the detection of C. tyrobutyricum (4). Among all the Clostridium and other bacteria tested, a specificity test revealed that the 21E7-B12 MoAb also detects C. butyricum and C. sporogenes (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The monoclonal antibody 21E7-B12 was used in an immunoenzymatic assay for the detection of C. tyrobutyricum (4). Among all the Clostridium and other bacteria tested, a specificity test revealed that the 21E7-B12 MoAb also detects C. butyricum and C. sporogenes (30).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this bacterium in milk can be determined using murine monoclonal antibodies (MoAb) raised against the outer cell wall (30). These MoAbs have also been used in an immunoenzymatic assay to detect C. tyrobutyricum cells (4) and have been applied to investigate their surface antigens. While little is known about the structure and antigenic properties of the cell wall of this bacterium, a previous biochemical study of the cell wall has shown that it contains a large amount of proteins composed mainly of one high molecular component (116 kDa), the major protein, that is readily released together with the flagellin by heating whole cells (6,17).…”
Section: Introductionmentioning
confidence: 99%
“…(21E7-B12) has been used in an immunoenzymatic assay to count C. tyrobutyricum cells in milk following membrane filtration (3). However, this MoAb detects not only the C. tyrobutyricum strains, but also, Clostridium sporogenes (strain PAO) and Clostridium butyricum (strain PA2).…”
mentioning
confidence: 99%
“…One of these antibodies, 21E7-B12 MoAb (IgG3 isotype), detects all C. tyrobutyricum strains as well as C. sporogenes (strain 545) and C. butyricum (Strain PA2). To detect these Clostridium in milk after membrane filtration, an immunoenzymatic test was developed using 21E7-B12 MoAb (3).…”
mentioning
confidence: 99%